PENGARUH BUDAYA ORGANISASI, PELATIHAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN KOPERASI MITRA SEJAHTERA DESA SIANGAN GIANYAR - Ni Putu Lia Enjalina; Sapta Rini Widyawati; Tiara Carina (VALUES, 2024)
The population in this study were 42 employees of the Mitra Sejahtera Cooperative, Siangan Gianyar Village. Regarding the sample, the sample in this study was 42 people who were determined using the census method or saturated sample. This research uses a number of data collection methods, both in the form of primary data and secondary data consisting of interview methods, questionnaires and documentation studies. To analyze the data, this research used five methods, including research instrument testing, classical assumption testing, multiple regression analysis, determination analysis, and t test. The results of the research show that Organizational Culture, Job Training and Compensation have a positive and significant effect on employee performance at the Mitra Sejahtera Cooperative, Siangan Village, Gianyar. This means that the better these three factors are, the more the performance of the Mitra Sejahtera Cooperative employees in Siangan Gianyar Village will improve.